A Comparison of Preservation Methods of Melientha suavis Pierre Branchlets under Low Temperature Condition - จูงกลาง, จารุณี; อุทัยบุตร, จํานงค์ (KKU Science Journal, 2014)
The preservation of Melientha suavis Pierre, Opiliaceae (pakwanpa) branchlets under low temperature (5±2 ºC) was compared in three tests: C1-uncovered branchlets, T1-branchlets covered with a plastic bag, and T2-branchlets covered with a wet cotton sheet. Weight loss (WL), chlorophyll a and b contents, malondialdehyde (MDA- a product of lipid peroxidation) content, electrolyte leakage (EL), and storage life of the branchlets were determined every three days. The results showed that WL, chlorophyll b content, MDA content, and EL of the branchlets increased with increasing time at 5 °C. In addition WL, MDA, and EL were lowest, but shelf life was longest in T1 method. The results from this study indicate that the best method in preservation of these branchlets is to keep them in a plastic bag which can maintain them for 6 days.